Transformation of the Human Image in the Paradigm of Knowledge Evolution - V. H. Kremen; V. V. Ilin (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The knowledge influence analysis on the formation process of new anthropological images of man in the contexts of scientific achievements and innovative technologies is the basis of this study. It involves the solution of the following tasks: 1) explication of the ontological content of knowledge in the anthropo-cultural senses of the epoch; 2) analysis of the knowledge influence on the process of forming a new type of man; 3) characteristics of the modern anthropological situation in the context of digital culture; 4) substantiation of interrelation of phatic communication with post-truth society in the dimensions of anthropo-social transformations of the present. Theoretical basis. Ontological content of knowledge determines the anthropo-cultural context of the epoch by forming a system of intellectual, value, social meanings of human life. The assertion of new anthropological types of man is caused by the changes in social and cultural space in the context of the growing influence of achievements in scientific knowledge and technology. Digital revolution as the process of expanding the possibilities of informational-digital reality, the substitution of knowledge for information gives rise to Homo digitalis – the digital man. He focuses on phatic communication, which in its intellectual meaninglessness is commensurate with the anthropological dimensions of post-truth society. Originality. It is substantiated that Homo digitalis is the result of a complex set of heterogeneous effects of scientific knowledge, which in modern post-truth conditions appears as different communicative practices. A condition for the formation of a new anthropological type of man in the perspective of scientific and technological progress is the affirmation of ethical wisdom. Conclusions. Knowledge in the process of evolution of socio-cultural life acquires constitutive significance for the process of formation of anthropological situations that manifest themselves in new images of man. Today, he is commensurate with the demands of digital culture, in which human life practices are increasingly becoming information and digital clusters embedded in the reality of a post-truth society. The means of overcoming the passivity of digital man is the formation of a new anthropological type based on a rethinking of the value system.